GANGSTER, GHOST, AND TRADITION: REPRESENTATION OF MARKET IN THREE INDONESIA FILMS - Rido Budiman; Novita Puspahaty; Dian Puspita Sari (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2023)
This research aims to determine what kind of market representation is displayed in three Indonesian films namely Di Bawah Lindungan Ka’bah, Gangster, Rumah Hantu Pasar Malam and how the viewers interpret it through various internet platform. The qualitative research design in the field of cultural studies especially the theory of representation and encoding-decoding from Hall is used to analyze data in the present study. By researching the above factors, we aim to provide more information toward the meaning of Indonesian films from the point of view of cultural studies.